Pengaruh Konsep Diri Terhadap Penyesuaian Diri Siswa Di SMA Negeri 3 Kota Jambi - Panigoro, R.A. Rafika; Sutja, Akmal; Yulianti, Yulianti (Indonesian Journal of Educational Counseling, 2024)
This study aims to discribe the level of self concept, the level of self adjustment and the influenceof self concept on student self adjustment at SMA Negeri 3 Jambi City. The study used a quantitative research with expost-facto method. The population this study were phase F class student of SMA Negeri 3 Jambi City with a sample of size 59 student taken from purposive technique. The data collection tool used is questionnaire with a likert scale and data analysis used through the percentage test and simple regression test. The result showed that the level of student self concept was at low level 36%, the level of student self adjustment was at low level of 32% and showed that self concept had significant effect on student self adjustment of 26,9% which was at a fairly strong level.